Design and preparation of highly structure-controllable mesoporous carbons at the molecular level and their application as electrode materials for supercapacitors. Issue 45 (14th October 2015) - Yan, Kun; Kong, Ling-Bin; Dai, Yan-Hua; Shi, Ming; Shen, Kui-Wen; Hu, Bing; Luo, Yong-Chun; Kang, Long
Abstract : The preparation process of highly structure-controllable mesoporous carbons (HSCMCs). Abstract : Highly structure-controllable mesoporous carbons (HSCMCs) were prepared through a simple carbonization procedure using well-controlled diblock copolymer precursors. We chose polyacrylonitrile- block -polymethylmethacrylate diblock copolymers as precursors, containing a source of carbon, i.e., polyacrylonitrile (PAN), and a sacrificial block, i.e., poly methyl methacrylate (PMMA). PAN- b -PMMA diblock copolymers were synthesized successfully by atom transfer radical polymerization (ATRP) in DMF at 90 °C with well-controlled molecular weight and narrow polydispersity. The as-synthesized PAN- b -PMMA diblock copolymers experienced a microphase-separation process to form a self-assembled nanostructure at 250 °C and then converted to a mesoporous carbon phase after carbonation at 800 °C. The mesoporous sizes of HSCMCs were increased with the increment of molecular weight of the sacrificial block (PMMA). In addition, the HSCMCs exhibited well-controlled mesoporous sizes of 5.96–17.42 nm and high specific surface areas of 427.6–213.1 m 2 g −1 . The well-controlled pore structure in such materials provided huge potential application as electrode materials for supercapacitors. In particular, HSCMC-5 with an optimal mesoporous size of 13.68 nm could achieve the highest specific capacitance of 254 F g −1 at a current density of 0.5 A g −1 in 2 M KOH aqueous electrolyte. Furthermore, it also possessed an excellent rate capability of 78% capacitance retention as the current density increased from 0.5 A g −1 to 5 A g −1 and a superior cycling performance of 96% capacitance retention after 10 000 cycles at a current density of 2 A g −1 . Besides, by precisely controlling the pore structure of HSCMCs, the mechanism of electric double layer capacitors could be investigated systematically.